Shame, guilt, and facial emotion processing: initial evidence for a positive relationship between guilt-proneness and facial emotion recognition ability. Issue 8 (16th November 2016) - Treeby, Matt S; Prado, Catherine; Rice, Simon M; Crowe, Simon F
ABSTRACT: Shame and guilt are closely related self-conscious emotions of negative affect that give rise to divergent self-regulatory and motivational behaviours. While guilt-proneness has demonstrated positive relationships with self-report measures of empathy and adaptive interpersonal functioning, shame-proneness tends to be unrelated or inversely related to empathy and is associated with interpersonal difficulties. At present, no research has examined relationships between shame and guilt-proneness with facial emotion recognition ability. Participants ( N  = 363) completed measures of shame and guilt-proneness along with a facial emotion recognition task which assessed the ability to identify displays of anger, sadness, happiness, fear, disgust, and shame. Guilt-proneness was consistently positively associated with facial emotion recognition ability. In contrast, shame-proneness was unrelated to capacity for facial emotion recognition. Findings provide support for theory arguing that guilt and empathy operate synergistically and may also help explain the inverse relationship between guilt-proneness and propensity for aggressive behaviour.